Evaluation of ADA activity as a potential marker of disease severity in psoriasis patients - Khan SA (Dove Medical Press, 2018)
Seraj Ahmed Khan,1 Sudha Agrawal,2 Nirmal Baral,1 Madhab Lamsal1 1Department of Biochemistry, B.P. Koirala Institute of Health Sciences, Dharan, Nepal; 2Department of Dermatology and Venereology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal Background: Psoriasis is a dermatological disorder with a multifactorial origin and is associated with many biochemical and immunological changes.  Purpose: This study aimed to examine the association of serum ADA activity, uric acid (UA), and high-sensitivity CRP (hs-CRP) with psoriasis and the role of ADA in disease severity.  Materials and methods: In this comparative cross-sectional study, 50 clinically and histopathologically diagnosed psoriasis patients and 50 age- and sex-matched healthy controls were enrolled. Blood samples were taken and analysis of the biochemical parameters was performed according to Giuisti and Galanti method, uricase and ELISA technique for ADA activity, UA, and hs-CRP, respectively. The severity of the disease was scored according to Psoriasis Area and Severity Index (PASI). Statistical analysis of differences within and between the study groups was carried out using the Student’s t-test, one-way post hoc ANOVA, and Pearson’s correlation. Linear regression was used to establish the independent association of ADA with disease severity.  Results: The serum ADA activity, UA, and hs-CRP levels of the psoriatic patients were found to be significantly higher (P<0.001). hs-CRP was positively correlated with ADA and UA in patients (P<0.001). There was no significant difference in total cholesterol, low-density lipoprotein, and triacylglycerol in psoriasis patients, whereas we noted a decreased high-density lipoprotein level in psoriasis patients as compared to controls. Linear regression showed that ADA was independently associated with the disease severity and was statistically significant (P<0.001).  Conclusion: ADA activity was positively and significantly associated with the severity of psoriasis, therefore, it could be suggested as a marker for disease severity in psoriasis patients. Keywords: adenosine deaminase, C-reactive protein, psoriasis, uric acid